BS EN ISO 10893-11 AMD1. Non-destructive testing of steel tubes. Part 11. Automated ultrasonic testing of the weld seam of welded steel tubes for the detection of longitudinal and/or transverse imperfections (2nd September 2019) - British Standards Institution,
No abstract available